Study on Prevalence and Pattern of Self Medication Practices in a Rural Area of Bihar - Pankaj Kumar; Arvind Kumar Vimal (Asian Journal of Medical Research, 2020)
Background: Self-medication is common in most parts. It leads to adverse effects. The present study was conducted to assess the pattern of self -medication and reasons behind this practice.Subjects and Methods:The present study was community based cross-sectional in nature conducted upon 198 adults residing in the rural field practice area. Sociodemographic profile and details of self-medication were noted.Results:63.1% of the respondents were males. 35.9% of them belonged to the age group of 30-40 years. 32.8% were illiterate and 85.9% were Hindu. A total of 198 respondents practiced self-medication (51.2%). Most common symptom was headache (85.9%). Common cold (63.1%), fever (56.1% and gas (31.8%) were other common complains. Paracetamol (90.0%), pantoprazole (51%), other NSAIDs (42.9%) and cold tablets (36.9%) were other medicines used commonly. 69.2% respondents said that they were practicing it for minor illnesses, 36.9% cited economic reasons while 46% said that consulting a physician needed much time and self-medication was time saving.Conclusion: Prevalence of self-medication is high. Strict drug regulations are needed.